2022
DOI: 10.3389/fphar.2022.993562
|View full text |Cite
|
Sign up to set email alerts
|

Daphnetin: A bioactive natural coumarin with diverse therapeutic potentials

Abstract: Daphnetin (DAP), a coumarin derivative extracted from Daphne species, is biologically active phytochemical with copious bioactivities including anti-inflammatory, anti-oxidant, neuroprotective, analgesic, anti-pyretic, anti-malarial, anti-bacterial, anti-arthritic, neuroprotective, hepatoprotective, nephroprotective, and anti-cancer activities. A wide range of studies have been conducted exploring the significance and therapeutic potential of DAP. This study reviewed various databases such as NCBI, PubMed, Web… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 121 publications
0
15
0
Order By: Relevance
“…We observed a significant downregulation in both TWT and MWT in rats after the intrathecal injection of daphnetin for 1 h. This effect lasted for 24 h. We reasonably speculated that the intrathecal injection of daphnetin was able to effectively improve NP in rats. The typical inflammatory pathway NF-κB and the release of inflammatory factors mediated by inhibiting the apoptosis proteins (IAPS) and cyclooxygenase-2 (COX-2) were also inhibited by daphnetin [ 16 ]. Some scholars pointed out that daphnetin was able to effectively inhibit the activation of glial cells in the spinal cord in inflammatory pain, which is related to its inhibition of the NF-κB pathway in the spinal cord [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed a significant downregulation in both TWT and MWT in rats after the intrathecal injection of daphnetin for 1 h. This effect lasted for 24 h. We reasonably speculated that the intrathecal injection of daphnetin was able to effectively improve NP in rats. The typical inflammatory pathway NF-κB and the release of inflammatory factors mediated by inhibiting the apoptosis proteins (IAPS) and cyclooxygenase-2 (COX-2) were also inhibited by daphnetin [ 16 ]. Some scholars pointed out that daphnetin was able to effectively inhibit the activation of glial cells in the spinal cord in inflammatory pain, which is related to its inhibition of the NF-κB pathway in the spinal cord [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Daphnetin (Dap), structured as 7,8-dihydroxycoumarin, as detailed in Figure 1 A, is the main active ingredient extracted from Daphne giraldii Nitsche, a plant of the family daphne, with a wealth of biological activities, including anti-inflammatory, antioxidant, neuroprotective, analgesic, and anticancer activities [ 16 ]. Daphnetin significantly inhibits the development of adjuvant arthritis by inhibiting the production of pro-inflammatory cytokines [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Scopoletin has been described in various anti-inflammatory and antioxidant activities [ 23 , 24 ], especially in identifying the modulation of NF-κB expression, mediated by Nrf2 [ 25 ], which allows us to suppose that both the extracts and fractions of B. ternifolia have a fully justified anti-inflammatory effect. In the joints, it is observed that the pathophysiological process of RA that developed secondary to the administration of CFA caused a significant increase in the production of TNF-α, IL-6, and IL-1β [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the joints, it is observed that the pathophysiological process of RA that developed secondary to the administration of CFA caused a significant increase in the production of TNF-α, IL-6, and IL-1β [ 3 ]. Allthe tested treatments derived from B. ternifolia , M4 could prevent the production of these proinflammatory cytokines, which may be related to ternifolial, which, as already mentioned, has an anti-inflammatory [ 23 , 24 ] and immunomodulatory effect [ 25 ]. Similarly, RA generates a significant increase in IL-17, which is associated with CD4+ T cells that promote inflammation, bone erosion, and cartilage degradation by the stimulating expression of NF-κB-specific activator receptor ligand (RANKL) and produce IL-17, which stimulates synovial macrophages and FLS [ 26 , 27 ] and to plasma cells that also promote inflammation through the production of cytokines and autoantibodies [ 14 , 28 ]; treatments based on extracts and fractions of B. ternifolia decreased the level of IL-17, particularly M3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation